1982
DOI: 10.3758/bf03212260
|View full text |Cite
|
Sign up to set email alerts
|

The effects of isolation and handling on reactivity to footshock and tactile dorsal stimulation

Abstract: The effects of isolation and handling on the reactivity of rats to two tactile stimuli were assessed in two experiments. In the first experiment, reactivity to more intense footshock was increased in rats raised in isolation but was not affected by handling by an experimenter. In the second experiment, increased reactivity to airpuff stimuli presented to the dorsal surface of isolation-reared rats was reduced by handling. The data suggest that the effects of handling on shock-motivated behaviors are not due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On the other hand, all subjects that were isolated from 26 to 40 days of age showed similar scores for the jumping threshold, which were lower than 0.30 mA irrespective of other differences in the rearing conditions. These facts suggest that isolation during the postweaning stage does not produce stress-induced hyperalgesia, reflected in the increased responsivity to nociceptive stimulus following exposure of a stressor (Illich, King, & Grau, 1995;Jørum, 1988;Vidal & Jacob, 1982, 1986Viken et al, 1982), but rather prevents the increase of the jumping threshold, which should increase with age under natural rearing conditions.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, all subjects that were isolated from 26 to 40 days of age showed similar scores for the jumping threshold, which were lower than 0.30 mA irrespective of other differences in the rearing conditions. These facts suggest that isolation during the postweaning stage does not produce stress-induced hyperalgesia, reflected in the increased responsivity to nociceptive stimulus following exposure of a stressor (Illich, King, & Grau, 1995;Jørum, 1988;Vidal & Jacob, 1982, 1986Viken et al, 1982), but rather prevents the increase of the jumping threshold, which should increase with age under natural rearing conditions.…”
Section: Figurementioning
confidence: 95%
“…Several studies, for example, have shown that the reactivity of isolated rats to electric shock increases (Sahakian & Robbins, 1977;Viken, Moore, Knutson, & Fordyce, 1982) while others have found it to decrease (Coudereau, Monier, Bourre, & Frances, 1997;Gentsch et al, 1988;Schwandt, 1993;Viveros et al, 1988). As for the reactivity to restraint, some studies have reported an increases in rats reared in isolation (Gamallo, Villanua, Trancho, & Fraile, 1986;Płaźnik, Pałejko, Stefański, & Kostowski, 1993) whereas others have shown a decrease in reactivity (Giralt & Armario, 1989).…”
mentioning
confidence: 99%